Fishy Business: Red Snapper Mislabeling Along the Coastline of the Southeastern United States - Spencer, Erin T.; Bruno, John F. (Frontiers in Marine Science, 2019)
Seafood mislabeling is a widely documented problem that has significant implications for human and environmental health. Defined as when seafood is sold under something other than its true species name, seafood fraud allows less-desired or illegally-caught species to be marketed as one recognizable to consumers. Red snapper is one of the most frequently mislabeled species, with previous studies showing mislabeling rates as high as 77%. We assessed whether red snapper mislabeling rates varied among states or vendor type. We also determined the stock status of substituted species to assess whether frequently substituted stocks were more or less at-risk than red snapper stocks. We used standard DNA barcoding protocols to determine the identity of products labeled as “red snapper” from sushi restaurants, seafood markets, and grocery stores in the Southeastern United States. Overall, 72.6% of samples (out of 62) were mislabeled, with sushi restaurants mislabeling samples 100% of the time. Out of 13 substituted species (including samples that were indistinguishable between two species), seven (53.8%) were not native to the U.S. Of the ten substituted species assessed by the IUCN red list, nine (90%) were listed as less threatened than red snapper. These results contribute to a growing body of mislabeling research that can be used by government agencies trying to develop effective policy to combat seafood fraud and consumers attempting to avoid mislabeled products.